OTUD3 suppresses the mTORC1 signaling by deubiquitinating KPTN - Li, Jiatao; Yang, Dan; Lin, Yan; Xu, Wei; Zhao, Shi-min; Wang, Chenji (Frontiers in Pharmacology, 2024)
Ubiquitination and deubiquitination modifications play pivotal roles in eukaryotic life processes, dysregulation can impact disease development such as tumorigenesis, regulating protein dynamics via the ubiquitin-proteasome pathway. OTU domain-containing protein 3 (TUD3), a deubiquitinase, stabilizes PTEN, suppressing tumor growth by inhibiting PI3K-AKT signaling. Yet, further OTUD3 substrates remain underexplored. Here, we demonstrate that, OTUD3 serves as a deubiquitinase for KPTN and interacts with it, facilitated by the OTU domain within OTUD3. Further investigations confirmed KPTN's ubiquitination modification, primarily at lysine residue 49. Ubiquitination experiments demonstrated OTUD3's ability to mediate KPTN's deubiquitination without affecting its protein levels, suggesting that KPTN's ubiquitination is a function-regulated, non-degradable modification. Under various amino acid starvation or stimulation conditions, overexpressing OTUD3 reduces mTORC1 signaling activation, while knocking out OTUD3 further enhances it. Notably, OTUD3's regulation of mTORC1 signaling relies on its deubiquitinase activity, and this effect is observed even in PTEN KO cells, confirming its independence from PTEN, a reported substrate. OTUD3 also promotes GATOR1's lysosomal localization, a process requiring the involvement of KPTN. Ultimately, OTUD3 affects cellular metabolic pool products by downregulating the mTORC1 pathway, significantly inhibiting tumor cell growth and proliferation. In summary, our findings shed light on an alternative perspective regarding the intrinsic functions of OTUD3 in inhibiting tumor development. We propose a novel mechanism involving KPTN-mediated regulation of the mTORC1 signaling pathway, offering fresh insights into the occurrence and progression of tumor diseases driven by related genes. This may inspire new approaches for drug screening and cancer treatment, potentially guiding future therapies for relevant tumors.